Pendampingan Penilaian Persediaan Pada BUM Desa Remasa Kekait Guna Implementasi Pelaporan Keuangan - Ramadhani, Rahmi Sri; Rakhmawati, Intan; Waskito, Iman (Universitas Mataram, 2025)
This community service was carried out in one of the wholesale grocery business units, at BUM Desa Remasa Kekait. This community service was held because BUM Desa Remasa Kekait had not implemented inventory management, so that it was difficult to know the amount of merchandise inventory. This community service aims to assist BUM Desa Remasa Kekait in managing inventory in the wholesale grocery business, so that it will be easier to determine the value of merchandise inventory, for the needs of preparing BUM Desa financial reports. In mentoring Activities at BUM Desa Remasa Kekait, the Community Service Team has prepared an inventory flowchart, that can be a Standard Operational Procedure (SOP) for Inventory Assessment, so that the inventory calculation method is easier to do. As a result, through warehouse cards or inventory cards and physical calculations (stock opname) of inventory, it is hoped that inventory assessment can be carried out more practically, and facilitate recording by BUM Desa employees. Community service activities are expected to continue to the next stage.